Aspects of brucellosis vaccination in Maranhão state - Paixão, Adriana Prazeres; Silva, Tânia Maria Duarte; Alves, Sara Ione da Silva; Rosário, Carla Janaina Rebouças Marques do; Santos, Hamilton Pereira; Bezerra, Danilo Cutrim; Bezerra, Nancyleni Pinto Chaves; Coimbra, Viviane Correa Silva (Frontiers in Microbiology, 2024)
Bovine brucellosis is a zoonosis of great economic and public health relevance. Understanding the epidemiological aspects of this disease is a determining factor to help developing effective strategies and supporting decision-making processes. The aim of the present study is to carry out a situational vaccination diagnosis against brucellosis in Maranhão State’s cattle in order to identify challenges set for vaccination operations and to help the Official Veterinary Service to plan health interventions. In 2022, questionnaires focused on the socioeconomic profile and knowledge on vaccination were applied to the following groups to help achieving the aforementioned aims: (i) cattle breeders (n = 201), (ii) veterinarians registered with the National Program for Control and Eradication of Brucellosis and Animal Tuberculosis (n = 84), (iii) Official Veterinary Service servants involved in conducting the National Program for Control and Eradication of Brucellosis and Animal Tuberculosis (n = 75), and (iv) individuals in charge of vaccine retail outlets (n = 58). Farmers and those in charge of vaccine retail outlets presented average knowledge on this subject (51–70% accuracy). Yet, there were similar knowledge gaps in these two groups. Although the knowledge level recorded for registered veterinarians and Official Veterinary Service servants was high (71–100% accuracy), low adherence to personal protection equipment was also observed, and it is worrisome, given brucellosis’ zoonotic nature. In addition, veterinarians presented knowledge gaps when it comes to updates on the National Program for Control and Eradication of Brucellosis and Animal Tuberculosis Technical Regulations, and it can be an indicative that questionnaires were superficially or carelessly answered. Other obstacles to vaccination were poor quality of roads to access properties and breeders with limited number of bred calves in the age group 3 to 8 months. These barriers impair the expansion of vaccination cover against brucellosis in Maranhão State. The Official Veterinary Service must implement a strategic plan to fill out the knowledge gaps shown by those in this production chain and make it easier to get to the basis for effective health interventions aimed at brucellosis control in Maranhão State.